Capn4 is a marker of poor clinical outcomes and promotes nasopharyngeal carcinoma metastasis via nuclear factor‐κB‐induced matrix metalloproteinase 2 expression. Issue 6 (21st May 2014) - Zheng, Pei‐Chan; Chen, Xiong; Zhu, Hong‐Wu; Zheng, Wei; Mao, Li‐Hua; Lin, Cheng; Liu, Jing‐Nan; Zheng, Ming
<x xml:space="preserve">Abstract</x> Calpain small subunit 1 (Capn4) plays a key role in tumor migration or invasion. In this study, expression and function of Capn4 was investigated in human nasopharyngeal carcinoma (NPC). Here we report that both mRNA and protein levels of Capn4 were elevated in NPC tissues when compared to normal NP tissues. Similarly, Capn4 was also highly expressed in multiple NPC cell lines, compared to immortalized human nasopharyngeal epithelial cell line NP69. Moreover, expression of Capn4 was significantly correlated with Epstein‐Barr virus infection, advanced stages, and lymph node or distant metastasis (P < 0.001). The patients with NPC displaying higher Capn4 had a significantly shorter overall survival (P = 0.002) and progression‐free survival (P = 0.003). Furthermore, siRNA knockdown of Capn4 suppressed cell migration and invasion in vitro and in vivo. These events resulted from Capn4 downregulation were associated with reduced expression of matrix metalloproteinase 2 (MMP2), Snail, and Vimentin. Finally, we demonstrated that Capn4 upregulated MMP2 via nuclear factor‐κB (NF‐κB) activation, manifested by increased phosphorylation of p65, a subunit of NF‐κB. Together, these findings argue a novel function of Capn4 in invasion and metastasis of NPC, and thereby suggest that Capn4 may represent an independent prognostic factor and a potential therapeutic target in NPC.